IMPROVING STUDENTS’ WRITING ACHIEVEMENT BY USING ANIMATION VIDEOS OF THE EIGHTH GRADE OF MTsN PARE - sarofah, umi (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
Expressing idea, thought, opinion and feeling through writing is the most difficult one in learning English. Therefore, the researcher decided to do this study whether animation videos can improve students’ writing achievement of the Eighth Grade of MTs N Pare. This study used Classroom Action Research (CAR) design. This study was conducted in VIII-I which consisted of 35 students, 11 males and 24 females. To know the implementation result of animation videos in students’ activity the researcher used observation checklist, field note, questionnaire, and interview. Meanwhile, to know the improvement of the writing achievement, test was used. Then researcher and collaborator observed the result by calculating the mean score and the percentage of classroom success. The research findings indicated that more than 80% students were more active and motivated in writing activity. In the first cycle the mean score was 73.66 with 57% subjects could achieve the criteria of success while students’ activity showed 60%. In the second cycle the mean was 85.03 with 91% subjects of could achieve the criteria of success while students’ activity showed 89%. Thus, students had positive attitude towards the use of animation videos. It can be concluded that animation videos can improve students’ achievement in writing.